1997
DOI: 10.1063/1.120209
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of GaN/AlGaN multiple quantum well microdisks

Abstract: Articles you may be interested inScattering (stochastic) recoupling of a coupled ten-stripe AlGaAs-GaAs-InGaAs quantum-well heterostructure laser Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…[4][5][6] Enhanced quantum efficiency ͑QE͒ and optical resonant modes have been observed in these microcavities. Most recently, we have fabricated electrically pumped InGaN/GaN QW individual -disk LEDs with a diameter of about 10 m and it was shown that the QE was higher in -disk LEDs than in the conventional broad-area LEDs.…”
mentioning
confidence: 98%
“…[4][5][6] Enhanced quantum efficiency ͑QE͒ and optical resonant modes have been observed in these microcavities. Most recently, we have fabricated electrically pumped InGaN/GaN QW individual -disk LEDs with a diameter of about 10 m and it was shown that the QE was higher in -disk LEDs than in the conventional broad-area LEDs.…”
mentioning
confidence: 98%
“…To improve the current spreading in LEDs with high Al molar fractions in the AlGaN cladding layers, an interconnected micro-pixel design has been adapted Wu et al, 2004). This use of micro-pixels was first introduced for III-nitrides by Mair et al (1997) to improve the light extraction from a AlGaN/GaN slab via the formation of microcavities, and the approach was then used in blue (Jin et al, 2000) and UV-A LEDs (Kim et al, 2003). The micro-pixel LED design was further extended to the formation of photonic crystals (Boroditsky et al, 1999) by the reduction of the size and the period of the array elements (Oder et al, 2003(Oder et al, , 2004).…”
Section: Deep-uv (Uv-b and Uv-c) Ledsmentioning
confidence: 99%
“…Recently, a significant enhancement of the quantum efficiency in the photoluminescence spectra has been observed by forming microdisks of about 9 m diam and 50 m spacing in GaN/ AlGaN multiple quantum wells ͑MQWs͒ and interpreted as a suppression of impurity transitions. 4,5 This letter reports the fabrication and photoluminescence characterization of Si/ Ge/Si single quantum well ͑SQW͒ microdisks of 0.5 and 1 m diam. We discuss significant changes in the light emissions from these structures, based on the near-band-gap luminescence of Si-Ge alloys 6 and Si/Ge superlattices.…”
Section: Enhancement Of Photoluminescence By Microdisk Formation Frommentioning
confidence: 99%